Chronic kidney disease as a cardiovascular risk factor: lessons from kidney donors - Price, Anna M. (J Am Soc Hypertens, 2018)
Chronic kidney disease (CKD) is a major risk factor for cardiovascular disease but is often associated with other risks such as diabetes and hypertension and can be both a cause and an effect of cardiovascular disease. Although epidemiologic data of an independent association of reduced glomerular filtration rate with cardiovascular risk are strong, causative mechanisms are unclear. Living kidney donors provide a useful model for assessing the “pure” effects of reduced kidney function on the cardiovascular system. After nephrectomy, the glomerular filtration rate ultimately falls by about one-third so many can be classified as having chronic kidney disease stages 2 or 3. This prompts concern based on the data showing an elevated cardiovascular risk with these stages of chronic kidney disease. However, initial data suggested no increase in adverse cardiovascular effects compared with control populations. Recent reports have shown a possible late increase in cardiovascular event rates and an early increase in left ventricular mass and markers of risk such as urate and albuminuria. The long-term significance of these small changes is unknown. More detailed and long-term research is needed to determine the natural history of these changes and their clinical significance.